Emotional Intelligence and Organisational Performance in Nepalese Commercial Banks - KC, Pradeep (Marsyangdi Journal, 2022)
The debate over the topics related to emotional intelligence (EI) and organisational performance has constantly been in discussion in different cultures and in different parts of the world. EI is an essential factor responsible for determining success in life and psychological well-being which plays an important role in better organisational performance. This article, therefore, has assessed the status of EI and organisational performance in Nepalese Commercial Banks and measured the impact of demographic factors on EI. It follows deductive research approach in which descriptive as well as analytical research design has been employed. The sampling units for the study consisted of 9 out of total 27 Nepalese commercial banks, and 67 respondents via convenience sampling with a structured questionnaire. Cronbach’s Alpha was calculated to confirm its reliability, which resulted in a score of 0.778. SPSS software package was used to manage and interpret data. The results of the study indicate that both emotional intelligence and organisational performance are present in the commercial banking sector. Analysis revealed that an employee with high emotional intelligence has a high organisational performance in comparison to a less emotionally intelligent person. The impact of matured employees is high on EI, here EI of a male is higher than female whereas the EI of married people is higher than unmarried. The results have implications for recruiting the employees. So, based on the results, it is recommended that an organisation must consider the emotional intelligence of the employees and emotional intelligence can be increased in the banking sector through different training and development programs.